2006
DOI: 10.1021/bi0613271
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Protein HMGN1 Modulates the Phosphorylation of Serine 1 in Histone H2A

Abstract: Here we demonstrate that HMGN1, a nuclear protein that binds specifically to nucleosomes, modulates the level of histone H2A phosphorylation. In Hmgn1 -/-cells, loss of HMGN1 elevates the steady-state levels of H2AS1ph throughout the cell cycle. In vitro, HMGN1 reduces the rate of Rsk2-and Msk1-mediated phosphorylation of nucleosomal, but not free, histone H2A. HMGN1 inhibits H2A phosphorylation by binding to nucleosomes since an HMGN mutant, which cannot bind to chromatin, does not inhibit the Rsk2-mediated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
(62 reference statements)
2
24
0
Order By: Relevance
“…Previous studies identified two general mechanisms that underlie the ability of HMGN1 to affect transcription by affecting nucleosomal histone modification (42,43,57,77) and by counteracting the ability of histone H1 to compact the chromatin fiber, mediated through the C-terminal CHUD domain (20,74). Our finding that the abundant HMGN1 interacts with specific DNA-binding transcription factors raised another possibility, that HMGN1 may squelch transcription factor activities.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies identified two general mechanisms that underlie the ability of HMGN1 to affect transcription by affecting nucleosomal histone modification (42,43,57,77) and by counteracting the ability of histone H1 to compact the chromatin fiber, mediated through the C-terminal CHUD domain (20,74). Our finding that the abundant HMGN1 interacts with specific DNA-binding transcription factors raised another possibility, that HMGN1 may squelch transcription factor activities.…”
Section: Discussionmentioning
confidence: 62%
“…The major members, HMGN1 and HMGN2, are present in the nuclei of all mammalian and most vertebrate cells, and have been studied for more than 30 years. It was demonstrated very recently that HMGN proteins can affect the PTM profile of core histones, indicating that HMGN may play a role in epigenetic regulatory mechanisms [60][61][62].…”
Section: Functions Of Hmg Proteins and Their Implications In Human DImentioning
confidence: 99%
“…The interaction of HMGN proteins with nucleosomes stabilizes the structure of the isolated CP, reduces the "compaction" of the higher-order chromatin structure (10), and alters the levels of posttranslational modifications in the tail of the nucleosomal histones (22,23,29,38).…”
mentioning
confidence: 99%